Caracterização citogenética de cultivares de feijão (Phaseolus vulgaris L.) - Nora, Gracieli Dalla (2012)
The meiotic behavior and estimation of pollen viability were studied in seven cultivars of common bean (Phaseolus vulgaris L.), which were IAPAR 44, Guapo Brilhante, BRS Expedito, BRS Valente, Guateian 6662, Pérola e Iraí. Floral buds were collected from cultivars, fixed and stored under refrigeration for the preparation of slides by squashing technique anthers and coloring with acetic orceína 2% and reactive Alexander. It was tried to obtain the greatest possible number of cells of each stage of meiosis. The estimation of pollen viability was observed by counting 800 pollen grains per plant. To verify changes in size, were measured 100 grains of pollen of each cultivar considered mature. There were no cells with abnormalities during the analysis of meiotic behavior in all cultivars. The meiotic index were high and uniform over 90%, indicating that these cultivars have the meiotic process stable and use in plant breeding not present problems. The pollen grains showed no significant differences as to its size, being similar among cultivars. Data on meiotic behavior and pollen viability obtained in this work combined with the literature, emphasize that the bean has a meiotic process uniform, showing high potential fertility of male gametes, which facilitates the use of this species in breeding programs.